Evaluation of antimicrobial activity of Aegle marmelos (L.) Corrêa and Cassia alata L. againsts pathogenic microorganisms - Veyakandah, Manivannan (2022)
Traditional medicine makes use of several plant species, including Aegle marmelos and Cassia alata, to cure a wide range of illnesses. The introduction of novel antibioticresistant bacteria and the spread of existing ones are major problems for public health around the world. The primary reason for conducting this research is to determine the efficacy of aqueous and methanol extracts of unripe fruit, A. marmelos leaves, and C. alata leaves against various microorganisms. Cold methanol and water extraction was used to extract the leaves and unripe fruit of A. marmelos and C. alata. Pathogenic bacteria (Streptococcus agalactiae, Escherichia coli, and Pseudomonas aeruginosa) and yeasts (Candida krusei and Candida parapsilosis) were tested for their susceptibility to the plant extracts using disc diffusion and agar well diffusion methods. Microdilution was used to establish the MIC and MFC, or minimal inhibitory and minimum fungicidal concentrations, respectively. Scanning electron microscopy (SEM) was utilised to examine the cellular modification induced by active plant extracts. The antifungal activity of the methanol extract of the fruit leaves of A. marmelos and C. alata was much higher than that of the water extract, which was ineffective against both C. parapsilosis and C. krusei. In contrast, the disc diffusion method did not detect any antibacterial activity from the methanol or aqueous extract. The minimum inhibitory concentration (MIC) for both A. marmelos leaf and C. alata unripe fruit against C. krusei and C. parapsilosis was found to be 75 mg/ml. However, the MIC for C. parapsilosis was reported to be 37.5 mg/ml. The MFC results for C. krusei and C. parapsilosis on A. marmelos leaf and unripe fruit and C. alata leaf all indicated 100% mortality at a concentration of 150 mg/ml. Fungistatic activity was demonstrated by the methanolic extract's minimal inhibitory and minimal fungigenic concentrations, respectively. The fungicidal and fungistatic properties of C. alata and A. marmelos leaves were demonstrated against C. parapsilosis and C. krusei. Under a scanning electron microscope (SEM), the effects of A. marmelos and C. alata methanol extract on C. parapsilosis and C. krusei were seen to cause a wide range of morphologic changes, such as wrinkles, breaks, bumps, holes in the cell wall, ruffles, and a raisin-like appearance. Based on these findings, A. marmelos and C. alata could serve as promising novel antifungal agent sources.